2018
DOI: 10.3892/ol.2018.7918
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ZEB2-AS1 promotes proliferation and inhibits apoptosis in human lung cancer cells

Abstract: Abstract. Lung cancer is among the leading causes of cancer-associated mortality worldwide, with a low 5-year survival rate of 16.1%. However, the underlying molecular mechanisms behind lung cancer tumorigenesis remain largely unknown. Long non-coding RNAs (lncRNAs) have been demonstrated to serve a function in the tumorigenesis of multiple types of cancer. The objective of the present study was to identify the function of a newly identified lncRNA zinc finger E-box-binding homeobox 2 antisense RNA 1 (ZEB2-AS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Previous studies have revealed up‐regulated lncRNA ZEB2‐AS1 in bladder, lung and pancreatic cancers and its overexpression associated with malignant clinicopathological features . To investigate the biological functions of ZEB2‐AS1 and its significance in HNSCC, we initially measured its expression via qRT‐PCR in 71 pairs of freshly collected HNSCC samples and adjacent non‐tumour mucosa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed up‐regulated lncRNA ZEB2‐AS1 in bladder, lung and pancreatic cancers and its overexpression associated with malignant clinicopathological features . To investigate the biological functions of ZEB2‐AS1 and its significance in HNSCC, we initially measured its expression via qRT‐PCR in 71 pairs of freshly collected HNSCC samples and adjacent non‐tumour mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…The lncRNA zinc finger E‐box binding homeobox 2 antisense RNA1 (ZEB2‐AS1) has attracted our attentions as it was highly expressed in several solid cancers like hepatocellular carcinoma, lung cancer and pancreatic cancer. Moreover, it usually promoted cell proliferation, invasion and EMT while inhibited apoptosis in diverse cancer contexts . These findings suggested that ZEB2‐AS1 was an oncogenic NAT with incompletely delineated roles in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…36 ZEB2-AS1 has been found to be highly expressed in many different types of cancer tissues and cells; meanwhile, it also proved to be an oncogenic lncRNA in human cancer by accelerating cell proliferation, invasion, and MET process. [24][25][26] Not surprisingly, this study found that ZEB2-AS1 was also highly expressed in CRC tissues. Moreover, by conducting a series of loss-of-function experiments, they identified that knockdown of ZEB2-AS1 attenuates the EMT process in CRC cell line, suggesting that ZEB2-AS1 indeed plays a regulatory role in the CRC pathologic process.…”
Section: Discussionmentioning
confidence: 49%
“…23 As a newly found tumor-associated lncRNA, zinc finger Ebox binding homeobox 2 antisense RNA 1 (ZEB2-AS1) was demonstrated to be highly expressed in many cancer cells. [24][25][26] However, the functional role of ZEB2-AS1 in CRC is yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, lncRNAs are pivotal regulatory molecules that are involved in diverse biological processes, including cell proliferation, cell-cycle progression, epithelial-mesenchymal transition (Cen et al, 2018), apoptosis (Y. Guo, Hu, Hu, He, & Li, 2018), differentiation (Gao, Ge, Li, Zhou, & Xu, 2018), and chromosome inactivation (Yue & Ogawa, 2018 (Hu, Jiang, & Jiang, 2017). Besides, the importance of lncRNA ANRIL in other diseases, like atherosclerosis (Chi et al, 2017) and diabetic retinopathy (Thomas, Feng, & Chakrabarti, 2017), have also been gradually reported.…”
Section: Discussionmentioning
confidence: 99%